Growth and development of the mulberry silkworm, Bombyx mori l. on vitamin B and c supplemented diet - Ahsan, Md Kamrul; Khan, Ataur Rahman; Ferdous, Tasnima (Bangladesh Journal of Zoology, 2015)
The effect of vitamin B and vitamin C on the growth and development of Bombyx mori L. has been studied. Oral supplementation of different concentrations of vitamin B and C to the 3rd, 4th and 5th instar larvae of multivoltine silkworm variety, BSR-95/14(M) resulted significant increase in larval and pupal characters. It was observed that the development of larvae and pupae took place up to a particular dose. There was also a significant increment in the various growth indices following vitamin supplements with the mulberry leaves. Bangladesh J. Zool. 41(2): 199-206, 2013